Pengaruh Metode Iqro’ Terhadap Kemampuan Membaca Al-Qur’an pada Anak Usia Dini di PAUD Baitul Qur’an Ranca Bungur - Agustina, Serly; Ikhtiono, Gunawan; Yono (Ikatan Da'i Indonesia, 2025)
Early childhood is an individual who is undergoing a rapid and fundamental development process, so learning to read the Qur'an from an early age is important to form a generation of Quranic intelligent and noble morals. The iqro' method as a systematic and gradual approach to learning to read the Qur'an is expected to make it easier for children to recognize the hijaiyah letters and read the Qur'an correctly. This study aims to analyze the effect of the iqro' method on the ability to read the Qur'an in early childhood at PAUD Baitul Qur'an Ranca Bungur and evaluate the supporting and inhibiting factors in its implementation. The research method used is quantitative with a correlational research design. Data were collected through questionnaires distributed to 52 PAUD Baitul Qur'an students, then analyzed using validity tests, reliability tests, normality tests, and simple linear regression to determine the effect of the Iqro' method on the ability to read the Qur'an. The results of the study indicate that the iqro' method has a positive and significant effect on the ability to read the Qur'an in early childhood. The average score of the iqro' method is 66.15 with a standard deviation of 14.301, while the average score of the ability to read the Qur'an is 51.73 with a standard deviation of 10.976. The use of this method can increase the fluency and accuracy of reading the Qur'an gradually and independently. Based on these results, it is recommended that PAUD Baitul Qur'an continue to optimize the use of the Iqro' method in learning to read the Qur'an, improve teacher training to support the application of the method, and create a conducive learning environment so that children are more motivated in learning the Qur'an.